2009
DOI: 10.1590/s0102-86502009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Arterial diameter of the celiac trunk and its branches: anatomical study

Abstract: Purpose: Despite the fact that anatomical variations of the celiac trunk are well explored in the literature, information on these vessels diameters is scanty. The aims of the present study were to describe the arterial diameters of the celiac trunk and its main branches, and to investigate if these diameters are altered in those cases presenting anatomical variations of these vessels. Methods: Twenty-one formalin fixed adult male cadavers were appropriately dissected for the celiac trunk identification and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 14 publications
5
46
0
12
Order By: Relevance
“…The previous study conducted by Tiwari 20 and Petrella 25 showed the origin of RIPA alone from the CT in 2% and 5.62%, LIPA alone in 4% and 21.35%, whereas both IPAs in 4% and 7.86% respectively. The origin of LIPA from the LGA is also described in the literature 7,21,22,33,38 . The knowledge of this type of variation shows that surgeons must be cautious to avoid unintentional sectioning of small calibre arteries, as it may occur during the coeliac artery decompression.…”
Section: Review Of Literature and Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The previous study conducted by Tiwari 20 and Petrella 25 showed the origin of RIPA alone from the CT in 2% and 5.62%, LIPA alone in 4% and 21.35%, whereas both IPAs in 4% and 7.86% respectively. The origin of LIPA from the LGA is also described in the literature 7,21,22,33,38 . The knowledge of this type of variation shows that surgeons must be cautious to avoid unintentional sectioning of small calibre arteries, as it may occur during the coeliac artery decompression.…”
Section: Review Of Literature and Discussionmentioning
confidence: 87%
“…bifurcation 10,11,13-18,21-23 , quadrifurcation 6,10,13,[15][16][17]19,20,22,[24][25][26] , pentafurcation 5,9,10,13,15,20,25,[27][28][29][30][31][32] , hexafurcation 13 , heptafurcation 33 and even absence 4,8,13,14,[16][17][18] of the trunk. Generally additional branches other than the normal branches are referred to as collaterals 5, 21, 27, 29, 32, 33 .…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Silveira et al suggested doing more studies on CT length and diameter based on above observations as they are useful for vascular surgeons and to prevent iatrogenic injuries. 9 Unfortunately to analyze further, CT diameter has not been measured in our study.…”
Section: Discussionmentioning
confidence: 92%
“…To the best of our knowledge, our study is the first to perform statistical comparison in a mixed sample selected under the same criteria and prove this assumption correct. Finally, few studies [36,72,92] have stated that existence of anatomic variation could alter a vessels' morphometry. We have chosen to discard cadavers presenting variations interfering with results of this study.…”
Section: Discussionmentioning
confidence: 99%